Diversidade de borboletas (Lepidoptera: hesperioidea e papilionoidea) em áreas verdes urbanas de Santa Maria, Rio Grande do Sul, Brasil - Lemes, Renata (2012)
Urban green areas can provide many feeding resources and conditions to harbor some animal species, especially small ones as insects. To analyze the diversity of butterflies in urban green areas in Santa Maria municipality, state of Rio Grande do Sul, 12 entomological net field samplings were carried out monthly from August 2010 to July 2011 on a gradient of urbanization. Sampling areas were: Presidente Vargas agene (PV) and Itaimbé Park (IP), located downtown, and Cemetery St. Rita (CSR), Mariano da Rocha Hill Monument (MMR) and Domingues Farm (SD). In 360 sampling hours, 2531 individuals were registered and distributed in 132 species. Of these, 57,36% belonged to the family Nymphalidae, 15,96% to Hesperiidae, 14,02% to Pieridae, 12,54% to Papilionidae, 2,68% to Lycaenidae and 2,37% to Riodinidae. Three butterfly species are new records for the State and 22 to Santa Maria municipality. SD presented the greatest richness and abundance of species and PV the lowest ones. About 33,33% of the species were exclusive from each one of the areas and 25% of these were singletons. Diversity indices of Shannon-Wiener and Margalef were higher in PV and PI and lower in SD. The dominance index of Simpson and Berger-Parker, were among representative at PV and PI in SD. The NMDS ordination showed a clear segregation of the studied areas, due to the urban gradient evaluated, forming distinct groups among themselves, peripheral and downtown areas, confirmed by the similarity analysis. The analysis showed that the percentage of dissimilarity of Pyrgus orcus (Stoll, 1780) and Junonia evarete (Cramer 1779) had a greater contribution to the differentiation of areas. The similarity between the species composition in peripheral areas was 48,45%, highlighting Actinote melanisans Oberthür, 1917 and Phoebis neocypris neocypris (Hübner, [1823]). The similarity of the downtown areas was 50,20%, greatest contribution of Hermeuptychia hermes (Fabricius 1775) and Junonia evarete (Cramer, 1779). Of all environmental variables measured, only "temperature" was correlated with the abundance of butterflies. Concluding, the butterfly fauna of urban green areas of Santa Maria municipality was very rich and abundant and had its diversity declined with the increasing urbanization gradient.